SISTEM PAKAR MENDIAGNOSIS PENYAKIT PADA TANAMAN TERONG BERBASIS WEB - Ardila, Sopia; Fajrin, Alfannisa (Computer Science and Industrial Engineering, 2022)
ABSTRACT Eggplant is a plant that has the Latin Solanum melogena which grows in tropical areas. Eggplant plants contain minerals, calcium and others. easy to cultivate, but eggplant is a plant that is easily attacked by plant diseases. The source of the problem lies in the farmers who have difficulty dealing with damage to eggplant plants caused by plant diseases so that farmers often experience losses during the harvest season. This plant disease usually appears during the rainy season so that the farmers' crop failure rate is very high. To reduce the risk of plant disease, a farmer needs to take proper care of this plant to avoid disease attacks. But at this of a farmer in how to overcome disease attacks on eggplant plants in determining the right treatment for eggplant plants. This is what can cause losses for farmers if they are late in handling and cause crop failure or damage to plants due to disease. In this case, the role of agricultural experts or agricultural experts is needed to analyze diseases in eggplant plants.